A decade‐long temporal analyses of human group‐A rotavirus among children with gastroenteritis: Prevaccination scenario in West Bengal, eastern India. Issue 8 (1st March 2020) - Chawla‐Sarkar, Mamta; Banerjee, Anindita; Lo, Mahadeb; Mitra, Suvrotoa; Okamoto, Keinosuke; Deb, Alok; Dutta, Shanta
Abstract: Despite the significant reduction in the global infantile death toll due to rotaviral diarrhea, India still contributes substantially to rotavirus‐related hospitalization as well as mortality rates. The rotavirus surveillance study conducted from 2008 through 2017 among children (≤5 years) with moderate to severe gastroenteritis seeking healthcare facilities at two hospitals in eastern India, revealed a change in the proportion of rotavirus positivity, seasonality, and age‐group specificity along with the cycling of different usual and unusual genotypes in this endemic setting. G1 strains predominated during 2008‐2010, while G2 and G9 genotypes eventually upsurged during 2011‐2013. G1 strains re‐established their lead during 2013‐2015, while G3 emerged for the first time in eastern India in 2015 and rooted itself as the cardinal strain 2016 onwards. Evolutionary analyses of all the predominant genotypes (G1, G2, G3, and G9) revealed that they were mostly phylogenetically distant to the rotavirus vaccine strains as depicted in the phylogenetic dendrogram. These decade‐long epidemiological studies during the pre‐vaccination period in West Bengal (eastern India) underscore the cocirculation of multiple rotavirus genotypes in addition to sporadic occurrence of zoonotic strains like G10P[6] and G11P[25]. Research Highlights: Decade long dynamics of circulating rotavirus strains in eastern India. Co‐circulation of multiple genotypes along with reassortant and zoonotic strains. Upsurge of polymorphic G3‐genotype in 2016‐17 for the first time in this setting. One‐fifth proportion of the strains was "unusual combination of usual genotypes". All the strains were phylogenetically distant to the rotavirus vaccine strains.